Collaborative Governance Dalam Pemberdayaan UMKM - Ruth Theda Rahmadevi; Diana Hertati (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
Micro, Small and Medium Enterprises (MSMEs) play a role in stabilizing the economy, because they have the potential to create jobs and reduce unemployment and poverty rates in a country. Rungkut Lor Village, Surabaya City is a forum for MSME groups engaged in the culinary sector, especially traditional snacks. However, there are still obstacles in its development that require collaboration with other sectors. The aim of this research is to find out and describe Collaborative governance in Empowering MSMEs in Kampung Kue, Rungkut Lor, Surabaya City using the Collaborative governance theory quoted by Emerson and Nabatchi Perdana et al., (2021), namely the dynamics of collaboration, action in collaboration and its impacts and adaptations are the result of collaborative action. The research method used is descriptive qualitative with data collection techniques through observation, interviews, documentation and literature study. The research results show that collaboration between stakeholders to empower MSMEs in Kampung Kue is already underway. However, in the process there has been no agreement or MoU between sectors responsible for empowerment.